Estudo de viabilidade econômica de geração de biogás para atender as necessidades de energia elétrica de uma unidade de suinocultura - Passaglia, Rúbia Carla (2019)
The global increase in investments in the area of sustainable energy is fundamental to the mitigation of problems associated with climate change and constitutes a great opportunity for economic and technological development, as well as the diversification of the energy matrix for many countries. The technology of the use of biodigestors presents itself as attractive in the treatment of agroindustrial residues, resulting in the generation of biogas and, consequently, electric energy, besides the biofertilizer. The general objective of this work was to conduct an economic viability analysis in the generation of electricity through biogas, in a pig farm located in the northern region of Rio Grande do Sul, through the NPV, IRR and the investment payback method. The economic viability analysis of this study was extremely feasible for the three calculated indicators, with a TIR of 24% and a payback of approximately 3 years and 8 months.